'New Breath' respiratory muscle trainer system for physical rehabilitation of cardiovascular pathology - Ivashchenko, A. S.; Ezhov, V. V.; Tsarev, A. Yu.; Dyshko, B. A. (Theory and Practice of Physical Culture, 2019)
Coronary heart disease is one of the main causes of mortality, disability and temporary disability in Russia.